The Effect Of Circuit Training To Improved Leg Muscle Power On Basketball Player - Dani Pramuno Putra (NHM PRESS, 1970)
Background: As basketball progress progresses at this time, a basketball player is required to have a good performance in a match. One of the factors affecting the performance of basketball players is the leg muscle power. Leg muscle power is the ability of the muscle to overcome the load with the speed of muscle contraction in a short time. Various training methods are given to support leg muscle power, for example the provision of circuit training. Circuit training is a training method that combines several training models into a unified training aimed at increasing the muscle power leg for better performance. Leg mucle power can be measured using the sargent jumpt test. Objective: This study was to determine the effect of providing circuit training to increase the leg muscle power of trained basketball players. Research Methods: The type of this study used the quasi experimental method with pre test and post test one group design, 15 male basketball players became samples with predetermined inclusion and exclusion criteria. The sample was made into one group, namely the group given the circuit training treatment which was carried out 3 times a week for 6 weeks. This study uses a Sargent Jump Test (SJT) measure. Normality test with Saphiro Wilk test. Hypothesis testing using paired sample t-test was used to determine the increase in muscle power leg in the treatment group. Results: There was a significant effect on the treatment group (p = 0,000).